2017
DOI: 10.1167/iovs.16-21023
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Activation of the Unfolded Protein Response Induces Cell Death in Fuchs' Endothelial Corneal Dystrophy

Abstract: Citation: Okumura N, Kitahara M, Okuda H, et al. Sustained activation of the unfolded protein response induces cell death in Fuchs' endothelial corneal dystrophy. Invest Ophthalmol Vis Sci. 2017;58:3697-3707. DOI: 10.1167/iovs.16-21023 PURPOSE. The unfolded protein response (UPR) is believed to play a role in the pathogenesis of Fuchs' endothelial corneal dystrophy (FECD). The purpose of this study was to investigate whether unfolded proteins accumulate in the corneal endothelium in FECD and if they are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 38 publications
2
32
0
Order By: Relevance
“…In addition, treatment options for preserving the release of functional ER calcium suppress cytokine-mediated beta cell death in diabetes 36 . Recently, ER stress was discovered to trigger the apoptosis of corneal endothelial cells through the intrinsic signaling pathway 37 , 38 . Thus, we postulated that the chronic elevation of aqueous cytokine levels may initiate the apoptosis of corneal endothelial cells via oxidative or ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, treatment options for preserving the release of functional ER calcium suppress cytokine-mediated beta cell death in diabetes 36 . Recently, ER stress was discovered to trigger the apoptosis of corneal endothelial cells through the intrinsic signaling pathway 37 , 38 . Thus, we postulated that the chronic elevation of aqueous cytokine levels may initiate the apoptosis of corneal endothelial cells via oxidative or ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…The same research group subsequently showed that homozygous knock-in of Col8a2 Q455K/Q455K , a causal gene for early-onset FECD, was sufficient to induce FECD-like ocular features in mice, and these changes were linked with UPR-associated apoptosis [ 40 ]. Recently, our group showed that ECM components, such as type I collagen and fibronectin, form aggregates of unfolded proteins in the corneal endothelium of FECD patients [ 41 ]. We also showed that activation of transforming growth factor-β (TGF-β) signaling causes a chronic overload of ECM proteins within the ER, which induces an accumulation of unfolded protein and activation of the intrinsic apoptotic pathway through the UPR [ 42 ].…”
Section: Pathophisiologymentioning
confidence: 99%
“…Accumulating evidence suggests that oxidative stress, induced by mitochondrial dysfunction, damages corneal endothelial cells. Interestingly, ER stress activates the intrinsic apoptotic pathway (the mitochondrial pathway) in the corneal endothelium, as it does in other cell types [ 41 ]. Future studies will likely elucidate the nature of the involvement of both ER stress and oxidative stress in the pathogenesis of FECD.…”
Section: Pathophisiologymentioning
confidence: 99%
“…The redox state within the cell affects ER protein folding machinery, and can result in Unfolded Protein Response (UPR) 41 , a cascade of signaling events that arise during ER stress. Studies in FCED have detected ER stress and UPR 22 . Here, we show that mitochondrial ROS, which could alter redox levels in ER, can also induce ER stress in the Slc4a11 KO model of CHED.…”
Section: Discussionmentioning
confidence: 99%
“…21 . Previous work has identified ER dysfunction in FCED 22 , and we further investigated whether mitoROS in Slc4a11 KO MCEC can affect ER stress.…”
Section: Er Stress and Unfolded Protein Response Is Activated In Slc4mentioning
confidence: 99%